2007
DOI: 10.1007/s11434-007-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Dihydroxybiphenyl dioxygenase gene was first discovered in Arthrobacter sp. strain PJ3

Abstract: Bacterium strain PJ3, isolated from wastewater and identified as Arthrobacter sp. bacterium based on its 16S rDNA gene, could use carbazole as the sole carbon, nitrogen and energy source. The genomic library of strain PJ3 was constructed and a positive clone JM109 (pUCW402) was screened out for the expression of dioxygenase by the ability to form yellow ring-fission product. A 2,3-dihydroxybiphenyl dioxygenase (23DHBD) gene of 933 bp was found in the 3360 bp exogenous fragment of pUCW402 by GenSCAN software an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… Péloquin and Greer (1993) obtained the gene cluster (DNA fragment, not the complete sequence information) contributed to the degradation of biphenyl and sequenced the partial sequence of bphC . Yang M. et al (2007) identified and characterized BphC in Arthrobacter PJ3. The identification of complete gene clusters involved in the degradation of biphenyl, especially the identification of the novel bph gene cluster, would advance the investigation of biphenyl metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… Péloquin and Greer (1993) obtained the gene cluster (DNA fragment, not the complete sequence information) contributed to the degradation of biphenyl and sequenced the partial sequence of bphC . Yang M. et al (2007) identified and characterized BphC in Arthrobacter PJ3. The identification of complete gene clusters involved in the degradation of biphenyl, especially the identification of the novel bph gene cluster, would advance the investigation of biphenyl metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Carbazole 1, 9 a-dioxygenase was encoded by carAaAcAd or carA; metacleavage enzyme was encoded by carBaBb or carB, and the meta-cleavage compound hydrolase was encoded by carC, respectively Genomic DNA of strain JS1 digested with XhoI was separated by electrophoresis in a 0.8% (w/v) agarose gel and blotted onto a nylon membrane. Gene Images TM DNA labeling and detection kit (Amersham Biosciences) were used as described elsewhere (Yang et al 2007). The probe used was 825 bp PCR fragment of carC from the car gene cluster (2,260-3,083 nt) of JS1.…”
Section: Isolation Of Carbazole-degradersmentioning
confidence: 99%
“…1). Marginal platform reef and shoal carbonates were first found in the Upper Permian Changxing Formation and the Lower Triassic Feixianguan Formation at the outcrops in the west of the Kaijiang-Liangping Shelf [3,4] . Therefore, the Yuanba area was recognized as a favorable place for marginal platform reef and shoal development.…”
Section: Introductionmentioning
confidence: 99%